Two new species and a new distribution record of the genus Malthodes Kiesenwetter (Coleoptera: Cantharidae) from Japan, with notes on the male and female abdominal morphology - Takahashi, Naoki; Imasaka, Shôichi (Zootaxa, 2020)
Two new species, Malthodes morimotoi sp. nov. and M. okushimai sp. nov., are described and illustrated from the western part of Japan. Additionally, M. parvus Kazantsev, originally described from the Russian Far East, is recorded from Japan for the first time. The male and female morphology of M. morimotoi sp. nov. was examined and noted in detail with specimens observed in copula.